Criminal Law in The Land Sector: Case Study in South Sumatra Regional Police - Daimon Daimon (NAROTAMA UNIVERSITY, Indonesia, 2020)
One of the natural wealth or natural resources created by God Almighty that is needed for human life is land. Humans live on land and obtain food by utilizing land. Human life cannot be separated from the land. The emergence of a legal dispute is originated from the objection of the guideline of a land right both to the status of the land, its priorities and ownership in the hope of obtaining administrative settlement in accordance with applicable regulations. This study uses normative juridical research methods so that the sources used are sourced from literature and legal literature. the conclusion in this study is The modus operandi in the occurrence of land disputes usually involves a systematic network between financiers, land speculators, land certificate brokers, thugs, regional government officials, the police and of course BPN elements. Commonly used modus operandi: Use of falsified land rights; Counterfeiting Warkah; Provision of false information; Letter forgery; Fictitious buying and selling; Fraud or embezzlement; Lease; Suing land ownership; Mastering thug-style land.